Rapid Communication: The loss of residual visual memories over the passage of time. Issue 2 (February 2015) - Mercer, Tom; Duffy, Paul
There has been extensive discussion of the causes of short-term forgetting. Some accounts suggest that time plays an important role in the loss of representations, whereas other models reject this notion and explain all forgetting through interference processes. The present experiment used the recent-probes task to investigate whether residual visual information is lost over the passage of time. On each trial, three unusual target objects were displayed and followed by a probe stimulus. The task was to determine whether the probe matched any of the targets, and the next trial commenced after an intertrial interval lasting 300 ms, 3.3 s, or 8.3 s. Of critical interest were recent negative (RN) trials, on which the probe matched a target from the previous trial. These were contrasted against nonrecent negative (NRN) trials, in which the probe had not been seen in the recent past. RN trials damaged performance and slowed reaction times in comparison to NRN trials, highlighting interference. However, this interfering effect diminished as the intertrial interval was lengthened, suggesting that residual visual information is lost as time passes. This finding is difficult to reconcile with interference-based models and suggests that time plays some role in forgetting.